PENGARUH MOTIVASI KERJA DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PT SREEYA SEWU INDONESIA UNIT RPAPARUNG BOGOR - Mochamad Bagus Ramadhan Bagus; Ana Septia Rahman (YBAMB, 2024)
Abstract This study aims to determine the influence of work motivation and leadership on employee performance at PT Sreeya Sewu Indonesia RPA Unit. The type of research used is quantitative research. The population in this study was employees of PT Sreeya Sewu Indonesia RPA Unit, totaling 150 people. Data analysis techniques in this research are using validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, multiple linear regression analysis, coefficient analysis, and hypothesis testing via the T test and F test. Based on partial analysis results The independent variable Work Motivation (X1) has a significant effect on the dependent variable Employee Performance (Y) at PT Sreeya Sewu Indonesia RPA Unit. This can be seen from the results of partial hypothesis testing (t test) where the calculated t value > t table (11.348 > 1.984) is obtained. This is also confirmed by the results of the significance value of 0.000 < 0.05, thus Ho1 is rejected and Ha1 is accepted. Based on the partial analysis results, the independent variable Leadership (X2) has a significant effect on the dependent variable Employee Performance (Y) at at PT Sreeya Sewu Indonesia RPA Unit. This can be seen from the results of partial hypothesis testing (t test) where the calculated t value > t table (7.856 > 1.984) is obtained. This is also confirmed by the results of the significance value of 0.000 < 0.05, thus Ho2 is rejected and Ha2 is accepted. Based on the partial analysis results, the independent variables Work Motivation (X1) and Leadership (X2) have a significant effect on the dependent variable Employee Performance (Y) at PT Sreeya Sewu Indonesia RPA Unit. This can be seen from the results of simultaneous hypothesis testing (f test) where the calculated f value > f table (72.177 > 3.090) is obtained. This is also confirmed by the results of the significance value of 0.000 < 0.05, thus Ho3 is rejected and Ha3 is accepted. Keywords: Work Motivation, Leadership, Employee Performance